Investigating the relationship between job resilience and organizational entrepreneurship in Payam Noor University, Fars province - Kouchakzadeh, Roghayeh; Behzadi, Sara; Sedaghat, Shahbaz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Background and purpose: presence in a turbulent environment and a competitive market, and the need for innovation drives entrepreneurs towards resilience. The requirement of entrepreneurs in organizations has led to innovation; Its primary purpose is to investigate the relationship between job resilience and organizational entrepreneurship. The geographical area of this research is Payam Noor University of Fars province. Methodology: The current research is descriptive-permanent research. This study used descriptive and inferential statistical methods for data analysis. The average test has been used to rank the components of job resilience and organizational entrepreneurship. Pearson's correlation coefficient test has also been used to measure the correlation between job resilience and organizational entrepreneurship. A regression model has been used to determine the contribution of each component of job resilience in organizational entrepreneurship. The most important tool for data collection in the current research was the questionnaire, measured using Cronbach's alpha coefficient and differential validity tests, as well as the reliability and validity of the questionnaire. Results: According to the analysis, there is a positive and strong correlation between job resilience and organizational entrepreneurship in Payam Noor University of Fars province. The characteristics of job resilience and organizational entrepreneurship are different between women and men and more among men than women. Conclusion: The contribution of resilience components in organizational entrepreneurship are, in order, willingness to change, risk-taking, networking, self-confidence, adaptability, independence, awareness of one's goals, willingness to do great work, awareness of trends, employability, and active learning.